One Indian girl - Bhagat, Chetan (New Delhi : Rupa Publicaitons India Pvt. Ltd, 2016)
Hi, I'm Radhika Mehta and I'm getting married this week. I work at Goldman Sachs, an investment bank. Thank you for reading my story. However, let me warn you. You may not like me too much. One, I make a lot of money. Two, I have an opinion on everything. Three, I have had a boyfriend before. Ok, maybe two. Bestselling author Chetan Bhagat, writing for the first time in a female voice, brings to you One Indian Girl, the heart-warming story of a modern Indian girl. Now if all this was the case with a guy, one might be cool with it. But since I am a girl these three things I mentioned don't really make me too likeable, do they?--Page 4 of cover.
Keywords: Indian women -- Fiction